CORE DESIGNS OF ABWR FOR PROPOSED OF THE FIRST NUCLEAR POWER PLANT IN INDONESIA - Yohannes Sardjono; Masanori Aritomi; Larry E. Fennern (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2011)
Indonesia as an archipelago has been experiencing high growth industry and energy demand due to high population growth, dynamic economic activities. The total population is around 230 million people and 75 % to the total population is living in Java. The introduction of Nuclear Power Plant on Java Bali electricity grid will be possible in 2022 for 2 GWe, using proven technology reactor like ABWR or others light water reactor with nominal power 1000 MWe. In this case, the rated thermal power for the equilibrium cycles is 3926 MWt, the cycle length is 18 month and overall capacity factor is 87 %. The designs were performed for an 872-fuel bundles ABWR core using GE-11 fuel type in an 9×9 fuel rod arrays with 2 Large Central Water Rods (LCWR). The calculations were divided into two steps; the first is to generate bundle library and the other is to make the thermal and reactivity limits satisfied for the core designs. Toshiba General Electric Bundle lattice Analysis (TGBLA) and PANACEA computer codes were used as designs tools. TGBLA is a General Electric proprietary computer code which is used to generate bundle lattice library for fuel designs. PANACEA is General Electric proprietary computer code which is used as thermal hydraulic and neutronic coupled BWR core simulator. This result of core designs describes reactivity and thermal margins i.e.; Maximum Linear Heat Generation rate (MLHGR) is lower than 14.4 kW/ft, Minimum Critical Power Ratio (MCPR) is upper than 1.25, Hot Excess Reactivity (HOTXS) is upper than 1 %Dk at BOC and 0.8 %Dk at 200 MWD/ST and Cold Shutdown Margin Reactivity (CSDM) is upper than 1 %Dk. It is concluded that the equilibrium core design using GE-11 fuel bundle type satisfies the core design objectives for the proposed of the firs Indonesia ABWR Nuclear Power Plant.Keywords: The first NPP in Indonesia, ABWR-1000 MWe, and core designs.   Indonesia adalah sebagai negara kepulauan yang laju pertumbuhan industri, energi, penduduk dan ekonominya cukup tinggi. Pada saat ini, jumlah penduduk Indonesia ada sekitar 230 juta dan 75 % dari jumlah penduduk tersebut tinggal di Pulau Jawa. Pada tahun 2022, dimungkinkan sistem jaringan Jawa-Bali dapat menerima beban 2 unit PLTN yang teknologinya sudah teruji seperti PLTN ABWR atau PLTN air ringan lainnya yang kapasitasnya masing-masing 1 GW. Untuk itu diambilah contoh perhitungan untuk PLTN ABWR pada siklus keseimbangan dengan daya termal 3926 MWt dan lama operasi 18 bulan dan kapasitas faktornya minimum 87 %. Desain ini telah dicapai dengan jumlah bahan bakar teras 872 bundel bahan bakar tipe GE-11 yang susunannya 9×9 batang bahan bakar yang ditengahnya ditempatkan 2 bahan bakar besar tiruan yang berisi air. Ada 2 langkah perhitungan; pertama adalah menggenerasikan pustaka data bundel bahan bakar dan selanjutnya digunakan untuk analisis termal dan reaktivitas dalam teras. Desain teras menggunakan kode komputer Toshiba General Electric Bundle Lattice Analysis (TGBLA) dan PANACEA. TGBLA adalah sebuah kode komputer yang dimiliki oleh General Electric Nuclear Energy untuk menggenerasikan pustaka data dalam sistem satuan cell dalam setiap batang bahan bakar dalam setiap bundle. PANACEA adalah kode komputer milik General Electric yang digunakan untuk analisis thermal hydraulic dan netronik yang digabung dalam simulator PLTN BWR. Hasil desain teras menguraikan tentang karakteristik termal dan reaktivitas teras seperti; laju maksimum pembangkitan panas linier (MLHGR) adalah lebih rendah dari 14,4 kW/ft, rasio daya kritis minimum (MCPR) adalah diatas dari 1,25, Reaktivitas Panas Lebih (HOTXS) adalah lebih besar dari 1 %Dk pada BOC dan 0,8 %Dk pada 200 MWD/ST dan reaktivitas shutdown margin dingin (CSDM) adalah lebih besar dari 1 %Dk. Untuk itu dapat disimpulkan bahwa desain teras PLTN ABWR pertama untuk diusulkan dibangun pertama di Indonesia dengan menggunakan bundle bahan bakar tipe GE-11 adalah telah memenuhi persyaratan dan tujuan desain. Kata kunci: PLTN pertama di Indonesia, ABWR-1000 MWe, dan desain teras.